2022
DOI: 10.1371/journal.pone.0268598
|View full text |Cite
|
Sign up to set email alerts
|

Personality growth after relationship losses: Changes of perceived control in the years around separation, divorce, and the death of a partner

Abstract: Background Previous research suggests that romantic relationships play a crucial role for perceived control. However, we know surprisingly little about changes in perceived control before and after the end of romantic relationships. Methods Based on data from the Socio-Economic Panel Study (SOEP), a nationally representative household panel study from Germany, we examined changes of perceived control in the years around separation from a partner (N = 1,235), divorce (N = 423), and the death of a partner (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
2
2
0
Order By: Relevance
“…Results from this study contribute to the literature by characterizing the trajectory and time-frame of stress response and recovery in young adults in the absence of intervention. These results are consistent with set-point theory (Asselmann & Specht, 2022a, 2022b) applied in the context of marriage and divorce. To our knowledge, this study is the first to document this trajectory in young adulthood.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Results from this study contribute to the literature by characterizing the trajectory and time-frame of stress response and recovery in young adults in the absence of intervention. These results are consistent with set-point theory (Asselmann & Specht, 2022a, 2022b) applied in the context of marriage and divorce. To our knowledge, this study is the first to document this trajectory in young adulthood.…”
Section: Discussionsupporting
confidence: 90%
“…Higher scores indicated greater levels of perceived control. Consistent with prior conceptualizations of control (Asselmann & Specht, 2022b; Skinner, 1996; Specht et al, 2013), we coded this variable as a binary variable split at the median score of 7 (0: high control, 1: low control).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ZM postulates that such an increase in the need for power engenders a decrease in an (infantile) need for security and an increase in the need for arousal, which can be considered additional manifestations of personality growth (Bowlby, 1982). This relationship is compatible with empirical research showing that personality growth has been found, among others, in reductions of neuroticism, increases in extraversion (e.g., Roberts et al, 2017), and more recently, in increases of perceived control (Asselmann & Specht, 2022). Accordingly, ZM would consider need changes as mechanisms underlying such modifications rather than temperamental factors.…”
Section: Relevance Of the Zurich Model For Personality Researchsupporting
confidence: 89%